Let's explore comets and asteroids - Orme, Helen; Orme, David, 1948 Mar. 1- (Tunbridge Wells, Kent : Ticktock Entertainment, 2007)
Explains what asteroids and comets are made of and where they come from, describes impacts with Earth, and discusses the history of scientific research into them.
The solar system -- What is an asteroid? -- Where are asteroids? -- Hunting for asteroids -- What is a comet? -- Where are comets? -- Comets and the Earth -- What can we see? -- Early sightings -- Space missions.
Includes index.
3-6.
Keywords: Asteroids -- Juvenile literature; Comets -- Juvenile literature; Asteroids; Comets; Asteroids; Comets